Enhanced electrical conductivity of suspended carbon nanofibers: Effect of hollow structure and improved graphitization. (November 2016) - Shilpa,; Das, Sudip Kumar; Afzal, Mohammad Atif Faiz; Srivastava, Shalabh; Patil, Sandip; Sharma, Ashutosh
Abstract: In this work we demonstrate that at the same pyrolysis temperature, higher graphitization can be attained in carbon nanofibers (CNFs) with hollow core compared to solid nanofibers, resulting in higher electrical conductivities in hollow CNFs. Through controlled electrospinning, single polymeric (PAN/PMMA) nanofibers are suspended across the walls of a photolithographically patterned SU8 microstructure, followed by pyrolysis to obtain single suspended solid, porous and hollow CNFs. It is found that hollow CNFs with a shell thickness of ∼35 nm demonstrate the highest electrical conductivity (∼10 5 S/m) which is almost an order of magnitude higher than those of solid CNFs (∼10 4 S/m). Further, porous CNFs of the same diameter show lower electrical conductivity compared to the solid fibers (∼10 3 S/m). The higher electrical conductivity of hollow CNFs is attributed to: a) its higher exposed surface area which results in a high amount of graphitic carbon at the surface during pyrolysis, b) increased polymer chain alignment in the thin shell region of precursor nanofibers that translates into an improved graphitic orientation on carbonization. Similar values of electrical conductivity were obtained by two-probe and four-probe methods, proving quantitatively that the contact resistance between the hanging CNFs and the underlying carbon structure is negligible. Graphical abstract: